AB1022 The recall survey: the relationship between ultrasound synovitis and bone erosion in patients with rheumatoid arthritis. (15th June 2017) - Filippucci, E; Bonali, C; Macchioni, P; Iagnocco, A; Sedie, A Delle; Tropea, S; Epis, O; Canzoni, M
Abstract : Background: Ultrasound (US) has shown to be a sensitive imaging tool for the detection of subclinical signs of synovitis in patients (pts) with rheumatoid arthritis (RA); further studies are still required to delineate the impact of US findings in the management of RA pts in daily clinical practice. Objectives: To investigate the relationship between US findings indicative of joint inflammation and US bone erosions at joint level in pts with RA. Methods: In 2015 an educational event focused on the added value of US in RA pts was held in 22 rheumatology centers in Italy. In every center, the local rheumatologists provided RA pts to be examined by US. Pts signed an informed consent and a brief history of them was collected by the local rheumatologists (previous and current therapy, DAS28, HAQ score). Bilateral US examinations of wrists, metacarpophalangeal (MCP) and metatarsophalangeal (MTP) joints were performed by rheumatologists expert in US, to assess synovitis (joint effusion, synovial proliferation, and power Doppler (PD) signal), and bone erosions, using a Logiq E R7, General Electrics, with a 4.2–13 MHz linear probe. All US findings were scored using a 4 degree semiquantitative scoring system. Results: In 465 RA pts, a total of 10.230 joints were scanned. Of these joints, 3.969 (39%) showed joint effusion and/or synovial proliferation and 1.784 (17%) were found positive for PD signal. The most frequently involved joints were the wrists followed by the second MCP joints and first MTP joints. In 749 joints US detected at least one bone erosion. The most frequently eroded joints were the wrists, the second and fifth MCP joints and the first and fifth MTP joints. A total of 226 RA pts showed at least one bone erosions and in 181 (80%) of these pts the eroded joints were found positive for PD signal. Conclusions: A high prevalence of PD signal was found in the joints found eroded by US. This is the first study providing such an evidence using a portable US equipment. Disclosure of Interest: None declared